Sequential application of major habit-reversal components to treat motor tics in children. - Woods, D W (1996)
In this study, we sequentially administered up to four components of the habit-reversal treatment to 4 children with motor tics within a multiple baseline design. The habit-reversal components included (a) awareness training; (b) awareness training and self-monitoring; (c) awareness training, self-monitoring, and social support; and (d) awareness training, social support, and the use of a competing response. Results demonstrated that the combined use of awareness training, social support, and competing response training was effective in eliminating motor tics in 2 of 4 children, that awareness training alone was effective for 1 child, and that a combination of awareness training and self-monitoring was effective for the 4th child. The treatment and ensuing improvement were found to be socially valid. We discuss possible explanations for these results and recommend directions for future research.